Safety of Anteromedial Portals in Elbow Arthroscopy: A Systematic Review of Cadaveric Studies: Anteromedial Elbow Cadaveric Review - Cushing, Tucker (Arthroscopy, 2019)
PURPOSE: To systematically review available literature comparing location and safety of two common anteromedial portals with nearby neurovascular structures in cadaveric models and to determine the correct positioning and preparation of the joint prior to elbow arthroscopy. METHODS: The review was devised in accordance with PRISMA guidelines. Inclusion criteria consisted of original, cadaveric studies performed by experienced surgeons on male or female elbows evaluating anteromedial portal placement with regards to proximity of the arthroscope to neurovascular structures. Exclusion criteria consisted of case reports, clinical series, non-English and non-cadaveric studies. Statistical analysis was done to measure reviewer reliability after scoring of each study. RESULTS: 2,596 studies were identified during screening and 10 studies met final inclusion as original, cadaveric investigations of anteromedial portal proximity to neurovascular structures. The difference in distance between proximal and distal portals was less than 1mm for the brachial artery and less than 1.5mm for the medial antebrachial cutaneous nerve, whereas the ulnar nerve was 4.17mm further from the distal portal and the median nerve was 5.07mm further from the proximal portal. Joint distension increased the distances of neurovascular structures to portal sites with the exception of the ulnar nerve in distal portals. Elbow flexion to 90 degrees increased distances of all neurovascular structures to portal sites. CONCLUSION: The results show proximal anteromedial portals puts less structures at risk compared to the distal portal. Elbows in 90-degrees flexion with joint distension carry a lower risk of neurovascular injury during portal placement. These findings suggest the proximal anteromedial portal to be the safer technique in anteromedial arthroscopy of the elbow. CLINICAL RELEVANCE: Discrepancies in placement of portals have existed in literature indicating differing safety margins regarding surrounding neurovascular anatomy. The present study aims to link the literature-based evidence together in order to describe the safest anteromedial portal variation.